A summary of 7q interstitial deletions and exclusion mapping of the gene for beta-glucuronidase. Issue 10 (October 1989) - Fagan, K; Gill, A; Henry, R; Wilkinson, I; Carey, B
Abstract : Three patients are described with different phenotypes and differing de novo interstitial deletions of the long arm of a chromosome 7. The first patient has a deletion with loss of the proximal 7q11.23 band. Only three other cases have been reported with this particular deletion. Our second case shows mild dysmorphism similar to the other four patients reported with deletion of bands 7q21.12—-21.3. Our third patient has a deletion of the 7q22.1—-32.2 segment and has many of the phenotypic features of the other reported cases of del 7q22—-32. GUSB, the gene for beta-glucuronidase, has been localised to the 7cen—-q22 region. Analysis of beta-glucuronidase levels in blood leucocytes of our patients has helped more precisely to assign this gene locus to 7q21.11 or 7q22.1.